Peritonsillar Abscess - Novad Sawelly; Baiq Najwa Shalfira Arka Kusuma; Muhammad Zahran Latif; Lalu Aditya Indrawahyu (International Journal of Public Health Excellence (IJPHE), 2026)
Peritonsillar abscess (PTA) is the most common deep neck space infection, predominantly affecting adolescents and young adults. This condition represents a suppurative complication of acute tonsillitis or pharyngitis, characterized by pus accumulation between the tonsillar capsule and the superior pharyngeal constrictor muscle. Despite advances in antibiotic therapy, PTA remains a significant clinical entity with potential for life-threatening complications if inadequately managed. This article provides a comprehensive overview of peritonsillar abscess, encompassing its etiology, epidemiology, pathophysiology, clinical manifestations, diagnostic approaches, and evidence-based management strategies. This study employed a qualitative comprehensive literature review method. Data were collected through systematic searching of electronic databases including PubMed, Scopus, and Google Scholar for articles published between 2010 and 2024. Additionally, retrospective data from Sanglah General Hospital Denpasar (2010–2017) were analyzed to provide Indonesian epidemiological context. The annual incidence of PTA approximates 30 cases per 100,000 population, with peak incidence in individuals aged 15–40 years. The condition is predominantly polymicrobial, with Group A Streptococcus recovered from approximately 20% of cases. Analysis of 38 Indonesian patients revealed male predominance (65.78%), mean age of 38.76 years, and Streptococcus viridans as the most commonly isolated organism (63.16%). Clinical presentation is characterized by unilateral sore throat, trismus, muffled "hot potato" voice, and uvular deviation. Diagnosis is primarily clinical, with needle aspiration serving as the gold standard. Management comprises prompt antibiotic therapy combined with surgical drainage. Peritonsillar abscess requires early recognition and appropriate intervention to prevent complications. A multimodal approach incorporating clinical assessment, imaging when indicated, and timely surgical drainage with targeted antibiotic therapy yields favorable outcomes.